Navigating boundaries: uncovering constraints in focus group discussion within the context of security issue - Thomas, Bibianah; Arapa, Afida; Nordin, Jennifah; Aning, Ibianaflorinciliana Niane Anthony; Jalil, Saiful Zizi (Research Management Centre (RMC), 2025)
Focus group discussion (FGD) is a crucial data collection strategy in qualitative research design. Using FGDs enables researchers to gather in-depth information from a large number of participants efficiently in terms of cost and effort. The advantage of FDGs is that they allow the collection of diverse perspectives from multiple participants simultaneously in a single location. However, despite their benefits, FDGs―like other research methods―have certain limitations that must be identified to implement appropriate mitigation measures. This paper aims to explore these limitations of FGDs. The researchers employed observation techniques during a series of FGDs in Sabah to examine security issues in the region. The study investigated the challenges experienced by both researchers and participants throughout the process. The findings reveal various constraints that emerged before (networking challenges, inappropriate site selection, last-minute cancellations), during (insufficient information, inadequate moderation skills, device issues, irrelevant information, time constraints, social desirability, groupthink, personality dynamics), and after (analytical constraints) the FGDs were conducted. These insights are expected to benefit future studies, particularly those in which FGDs are being considered as the data collection method.